Structural analysis of mixed alkali borosilicate glasses containing Cs+ and Na+ using strong magnetic field magic angle spinning nuclear magnetic resonance*. Issue 1 (1st March 2017) - Kaneko, S.; Tokuda, Y.; Takahashi, Y.; Masai, H.; Ueda, Y.
Abstract: We have investigated the local structure of alkali atoms in mixed alkali silicate, borate, and borosilicate glasses, which contain Cs + and Na +, using strong magnetic field magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy of 133 Cs and 23 Na. The spectral peaks of 133 Cs in borosilicate (Si:B = 1:1) and Si-rich borosilicate (Si:B = 2:1) glasses shifted to upfield with increasing Cs + /(Na +  + Cs + ) ratio, which implies that the coordination number of Cs + decreased as in the case of silicate and borate glasses. However, this trend was not observed in the 23 Na spectra of either borosilicate glass. This might be because the chemical shift of 23 Na in borosilicate glass is strongly affected by nearby species such as Si or B, and not by the coordination number of Na + .